(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a comprehensive analysis of the integration of artificial intelligence (AI) technologies into the medical education system, their interaction with pedagogical mastery, and their impact on the quality of education. In modern medical education, it is essential not only to acquire theoretical knowledge but also to develop clinical thinking, practical skills, and communicative competencies. From this perspective, the effectiveness of innovative pedagogical technologies—including AI-based systems, simulation-based learning, interactive methods, and digital platforms—is scientifically examined. The article also addresses the contemporary requirements of pedagogical mastery, its structural components, and the issue of teachers’ digital competence. The results of the study indicate that the integration of pedagogical mastery and artificial intelligence technologies plays a significant role in enhancing the effectiveness of medical education.